A real case study on the selection of suitable roll stabilizer type for motor yachts using hybrid fuzzy AHP and VIKOR methodology. (1st December 2020) - Demirel, Hakan; Şener, Bekir; Yildiz, Burak; Balin, Abit
Abstract: The comfort of passengers is one of the most important issues on yachts, both during cruising and at anchor position. For this reason, various stabilization equipment is used to minimize the movements resulting from the forces that expose to the yachts at sea. Determining the most suitable stabilization system for a yacht is a challenging multi-criteria decision making (MCDM) problem that requires evaluating many different criteria together. In this study, it is aimed to reveal a hybrid AHP (Analytical Hierarchy Process) and VIKOR (VlseKriterijumska Optimizacijia I Kompromisno Resenje) methodology that can be applied to similar practical problems. A group of decision-makers was asked to evaluate and compare fifteen criteria in the selection of roll stabilizer and evaluate the relationship status of the determined criteria for four alternatives through a questionnaire. The evaluations of the decision-makers were analyzed through the proposed methodology and the results were presented and discussed. Highlights: A hybrid fuzzy AHP-VIKOR methodology was presented for practical MCDM problems. 2. Proposed methodology was applied to stabilizer selection problem for motor yachts. 3. Alternatives were ranked by using the weights of the criteria. 4. Sensitivity analysis was performed to evaluate the robustness of the methodology. 5.